(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article presents a clinical case of the development of intermittent claudication in a patient with Leriche syndrome, who for 25 years had been abusing bad habits such as: smoking - 1 pack in 1.5 days, smoking experience - over 20 years. Black, strong coffee over 5 cups a day, which, according to our observations, are harbingers of the development of chronic ischemia of the pelvic organs and lower extremities. The influence of risk factors at such an early age is described, as a result of which the quality of life deteriorated, the ability to work decreased with the subsequent development of disability.